UPAYA PENYELESAIAN KONFLIK SUKSESI KRATON SURAKARTA MELALUI PENDEKATAN KEARIFAN LOKAL - Dirga Candra Styawan; Deni Zein Tarsidi; Muhammad Hendri Nuryadi (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
The succession conflict at the Surakarta Palace following the deaths of Pakubuwana XII and XIII threatens cultural cohesion and institutional stability. This study aims to formulate a conflict resolution strategy through the Javanese local wisdom approach. Employing a qualitative method with literature review techniques, this research analyzes power dynamics, root causes of the dispute, and the relevance of cultural values in contemporary contexts. The theoretical framework integrates sociological perspectives that view conflict as an inherent phenomenon and a functional mechanism driving social transformation. Findings indicate that effective resolution requires two complementary mechanisms: first, internal family dialogue within the palace that internalizes the principles of consensus-based deliberation, respect for traditional hierarchy, and harmony; second, the involvement of a neutral third party as a cultural mediator to ensure objectivity and alignment with customary regulations (paugeran). The synergy of these approaches produces a legitimate and sustainable resolution model. Succession conflict is thus reframed not as a threat of disintegration, but as an opportunity for institutional revitalization. Implementing this strategy strengthens the Surakarta Palace's role as a guardian of adaptable Javanese civilization, while demonstrating the continued relevance of local wisdom in modern conflict management.